EVALUASI KINERJA LAYANAN ANGKUTAN PENGUMPAN BUS TRANSJAKARTA RUTE LEBAK BULUS-SENEN - Putra, Adnan Kusuma; Tangkudung, Ellen S.W. (Jurnal Transportasi, 2018)
Abstract PT Transjakarta together with the private operators synergizes to increase the feeder bus service in the coverage area around Jakarta. One of them is Lebak Bulus-Senen feeder service, on the 6H Transjakarta corridor service. Based on static and dynamic surveys, the results of this service evaluation show that the number of buses provided is not able to meet the existing passenger demands, which is indicated by the value of the busload factor which shows the number of passenger needs is high, but the waiting time of passengers is greater than the bus arrival time. The number of fleets currently available is also unable to meet the standard services. Based on the travel time, the required bus fleet is 35 units, while in practice only 26 units of vehicles were operated. Therefore a re-plan is necessary by considering the addition of bus unit so that the implementation of Transjakarta Lebak Bulus-Senen feed service is in accordance with the passenger demands and meet the Minimum Service Standard of Transjakarta. Keywords: feeder bus, feed service, waiting time, load factor  Abstrak PT Transjakarta bersama dengan pihak operator swasta bersinergi untuk menambah layanan bus pengumpan di wilayah jangkauan di sekitar Jakarta. Salah satunya adalah layanan pengumpan Lebak Bulus-Senen koridor 6H Transjakarta. Berdasarkan survei statis dan survei dinamis, hasil evaluasi layanan ini menunjukkan bahwa jumlah armada bus yang disediakan tidak mampu memenuhi permintaan penumpang yang ada, yang ditunjukkan oleh besarnya nilai faktor muat bus yang memperlihatkan jumlah kebutuhan penumpang yang tinggi, namun waktu tunggu penumpang lebih besar daripada waktu kedatangan bus. Jumlah armada yang ada saat ini juga tidak mampu memenuhi pelayanan standar. Berdasarkan waktu tempuhnya, armada bus yang dibutuhkan adalah 35 unit, sedangkan dalam praktiknya hanya dioperasikan 26 unit kendaraan. Karena itu diperlukan perencanaan ulang dengan mempertimbangkan penambahan unit bus agar pelaksanaan layanan pengumpan Transjakarta Lebak Bulus-Senen sesuai dengan kebutuhan penumpang dan memenuhi Standar Pelayanan Minimal Transjakarta. Kata-kata kunci: bus pengumpan, layanan pengumpan, waktu tunggu, faktor muat